2012
DOI: 10.1111/j.1750-3841.2012.02877.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Antimicrobial Susceptibility of Listeria monocytogenes Isolated from Brined White Cheese in Jordan

Abstract: Listeria monocytogenes is a serious foodborne pathogen that has been isolated from different dairy food products. Several foodborne outbreaks of listeriosis have been associated with consumption of cheese. The aims of this study were to determine the occurrence of L. monocytogenes and Listeria spp. in brined white cheese (BWC) sold in Jordan, and to determine the susceptibility of isolated L. monocytogenes to antimicrobials. Three hundred and fifty samples of 5 different types of BWC (akkawi, boiled, halloumi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
1
24
3
1
Order By: Relevance
“…Our results were contradicted in another study conducted in Jordan by Osaili et al [19] who reported approximately 30% L. monocytogenes sample contamination rate. It should be noted that the contamination rate of Listeria in dairy products in our study was consistent with the results of [14].…”
Section: Discussioncontrasting
confidence: 57%
“…Our results were contradicted in another study conducted in Jordan by Osaili et al [19] who reported approximately 30% L. monocytogenes sample contamination rate. It should be noted that the contamination rate of Listeria in dairy products in our study was consistent with the results of [14].…”
Section: Discussioncontrasting
confidence: 57%
“…Surprisingly, E. coli 0157:H7 was not isolated from any of these products, although this pathogen was isolated previously from raw beef in Jordan at a rate of 7.8% (30). The findings in the current study are promising in comparison with earlier reports on the prevalence of L. monocytogenes in RTE products in Jordan (29,32). In Amman, Osaili et al (29) found L. monocytogenes prevalences of 13.3, 76.7, and 30% in chicken shawirma, chicken burger, and chicken sausage, respectively.…”
Section: Discussioncontrasting
confidence: 41%
“…Assessment of the food safety status and microbiolog ical quality of RTE foods available to consumers in Jordan is one of the major priorities for the Jordan Food and Drug Administration (JFDA), but few studies on the prevalence of foodbome pathogens in RTE food products in Jordan have been published (1,2,29,32). The objectives of the current study were to determine the prevalence Salmonella, L. monocytogenes, and E. coli 0157:H7 in Mediterranean RTE meat products sold in restaurants in Jordan and to determine the susceptibility of the isolates to selected antibiotics.…”
mentioning
confidence: 99%
“…In soft cheese about 1 (2%) out of 50 samples were found positive for L. Monocytogenes by PCR. Our results were contradicted to other study conducted in Jordan by Osaili et al [20] where they were reported about 30% of pathogenic L. monocytogenes in soft cheese. It should be noted that the pathogenic L. monocytogenes in our research for the contamination rate of Listeria in dairy products, cheese are consistent with the results indicated by Jalali and his team [16].…”
Section: Discussioncontrasting
confidence: 57%